Tumour-induced osteomalacia due to an intra-abdominal mesenchymal tumour. Issue 12 (4th December 2019) - Krishnappa, Brijesh; Jadhav, Swati Ramteke; Lila, Anurag R; Bandgar, Tushar R
Abstract : A 50-year-man presented with debilitating lower-limb proximal muscle weakness and hip pain since 3 years. Investigations (serum calcium (8.9 mg/dL), serum phosphorus (1.5 mg/dL), serum albumin (40 g/L), parathyroid hormone (116 pg/mL (12.30 pmol/L)), 25(OH)D3 (25.2 ng/mL (63 nmol/L)) 1, 25(OH)2 D3 (19 pg/mL (45.60 pmol/L)), tubular reabsorption of phosphate of 0.22 and elevated serum fibroblast growth factor 23 (FGF23) (387.7 RU/mL)) were consistent with tumour-induced osteomalacia (TIO). Localisation studies ( 68 Ga DOTATATE positron emission tomography (PET)/CT and 18 FDG-PET/CT) did not reveal any lesion. Re-evaluation after 2 and 5 years with 68 Ga-DOTANOC PET/CT showed 2×1.4 cm progressively increasing rounded soft tissue enhancing mass close to splenic hilum (SUV max: 26.4). Tumour was resected by laparotomy. Both FGF23 (120 RU/mL on day 3) and serum phosphorus (2.5 mg/dL on day 10) normalised with significant clinical improvement after surgery. Histopathology revealed phosphaturic mesenchymal tumour. Here, we report the first case of intra-abdominal mesenchymal tumour causing TIO diagnosed by serial functional imaging.